2019
DOI: 10.5325/jeasmedarcherstu.7.3.0299
|View full text |Cite
|
Sign up to set email alerts
|

Anatolian Empires: Local Experiences from Hittites to Phrygians at Çadır Höyük

Abstract: Çadır Höyük provides rich evidence for the endurance and transformation of specific cultural features and phenomena at a rural center on the Anatolian Plateau as it experienced the waxing and waning of control by imperial political powers of the Bronze and Iron Ages. Especially evident for those periods is the construction and maintenance of public architecture during periods of imperial power; certain economic activities also shift in their importance at those times. At the same time, continuity in economic a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…As observed by ref. 122 : “depending on one’s geographic location … the end of the Hittite Empire might have felt more like a bump or a bang”. As noted earlier, ‘collapse’ is thus rather best viewed as a form of transformation and so resilience.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…As observed by ref. 122 : “depending on one’s geographic location … the end of the Hittite Empire might have felt more like a bump or a bang”. As noted earlier, ‘collapse’ is thus rather best viewed as a form of transformation and so resilience.…”
Section: Methodsmentioning
confidence: 99%
“…What has been absent is evidence of a specific but potentially historically transformative multi-year severe drought. However, at the same time, while many studies concentrate on the widespread evidence for collapse in the period around and following ~1200 bc 4,[17][18][19]109,114 , it is important to observe that, while widespread, collapse was by no means universal, and, at a number of sites (and areas), there is rather evidence of continuation, reorientation or even development during this time, and differential site and regional impacts and trajectories are observed 20,26,28,38,57,59,117,[119][120][121][122] . In the case of the Hittites, in particular, it is the Hittite Empire and its central administration and the site of Hattusa (capital and religious centre or core), especially, that collapses (ending also the primary textual history available from the Hittite world until that time).…”
Section: Hittite and Ancient Near Eastern History Geography And Chron...mentioning
confidence: 99%
“…Scholars have suggested that only the Hittite elites abandoned the capital (Seeher 2001;, and that the decades before the fall of the Empire -around 1180 BC or later -were rather a period marked by changes in the administrative workings of society and several internal and external problems (Schachner 2020). Some sites were abandoned, some rebuilt more modestly, and others were still continuously occupied without significant interruption (Mielke 2011;Ross et al 2019). Therefore, it was suggested that the Early Iron Age (ca.…”
Section: Introductionmentioning
confidence: 99%
“…This might suggest that the central plateau, within which Çadır Höyük rests, would then exist as its own regional and cultural entity, but the ceramic evidence does not confirm this Çadır Höyük rests within the bend of the Kızılırmak (river) in the province of Yozgat (Figures 1-3). Since 1994, continuous excavations have revealed 6000 years of occupation on the Çadır mound, spanning the late sixth millennium BCE to the 14th century of this era (Cassis et al 2019;Ross et al 2019a;Steadman et al 2019a). Excavations on all four slopes of the mound, as well as on the North Terrace, have revealed the fortifications built by residents during the second millennium BCE Hittite age (Ross et al 2019b;, and the various industries undertaken during the Iron Age (first millennium BCE) Phrygian and later empires (Steadman et al 2019b, forthcoming).…”
Section: Introductionmentioning
confidence: 99%